Polymer Gels Science and Fundamentals - Thakur, Vijay Kumar; Thakur, Manju Kumari; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book exclusively focuses on the science and fundamentals of polymer gels, as well as the numerous advantages that polymer gel-based materials offer. It presents a comprehensive collection of chapters on the recent advances and developments in the core science and fundamentals of both synthetic and natural polymer-based gels, and pays particular attention to applications in the various research fields of biomedicine and engineering. Key topics addressed include: polysaccharide-based gels and their fundamentals; stimuli-responsive polymer gels; polymer gels applied to enzyme and cell immobilization; chitosan-based gels for cancer therapy; natural polymeric and gelling agents; radiation dosimetry; polymeric gels as vehicles for enhanced drug delivery across the skin; transport in and through gel; and polymer gel nanocomposites and functional gels. The book's extensive and highly topical coverage will appeal to researchers working in a broad range of fields in industryand academia alike.
Brea Gum Gel Capacity -- An Overview on Polymer Gels Applied to Enzyme and Cell Immobilization -- Xylan-Based Gels and Their Fundamentals -- Stimuli-Responsive Polymer Gels for Protein Delivery -- Polysaccharide-Based Polymergels -- Chitosan Based Gels for Cancer Therapy -- Natural Polymeric and Gelling Agents -- Radiation Dosimetry - A Different Prospective of Polymer Gel -- Polymeric Gels: Vehicles for Enhanced Drug Delivery Across Skin -- Graphene Oxide - Polymer Gels -- Transport in and Through Gel -- Strategizing Advance Application of Polymer Gels by Incorporation of Fillers -- Polymer Gels: New Materials for the Future -- Polymer Gel-Clay (Nano)Composites -- Functional Gels -- Molecular Distinction Between Structures of Nanoporous Siloxane Polymers -- Stimuli Responsive Polysaccharides Based Gels: Fundamental and Pharmaceutical Aspects -- Polymer Gel for Islet Encapsulation for Diabetes Therapy.
Keywords: Polymers; Biomedical engineering; Pharmaceutical chemistry; Polymers; Biomedical Engineering and Bioengineering; Pharmaceutics